Democracy Under Pressure : An Introduction to the American Political System, 2006 Election Update - Cummings, Milton C. (Thomson Wadsworth, 2007)
This book gives you a balanced, realistic guide to American politics that clearly describes the institutions of American government. The theme of democracy under pressure helps you focus on the way the American democracy responds to needs and demands of its people. The respected the team of Cummings and Wise provide in-depth coverage of the 2006 mid-term elections, the long-term threat of terrorism, issues surrounding the continuing conflict in Iraq, an analysis of the Department of Homeland Security and FEMA, recent intelligence reforms, warrantless wiretapping, and hundreds of other late-braking topics! Democracy Under Pressure focuses on the gap that exists between rhetoric and reality in government today.